Lucid music: a pilot study exploring the experiences and potential of music-making in lucid dreams - Schädlich, Melanie; Erlacher, Daniel (Dreaming, 2018)
In a lucid dream, the dreamer knows that he or she is dreaming and can thus deliberately carry out actions. The original goal of this study was to investigate musical practice in lucid dreams and its possible effects as well as the quality of the experiences. A total of 5 musicians were interviewed about their lucid dreams in which they had played instruments and sung. However, the interviewees were more interested in pleasure and inspiration than in actual practice and skill improvement. Therefore, the results provide more general information than planned. It could be shown that singing and playing musical instruments mostly work well in lucid dreams. Lucid music dreams were often accompanied by positive emotions and led to several positive effects in waking life, like facilitated guitar playing and enhanced confidence. Two interviewees especially enjoyed improvising solo in lucid dreams. The participants also emphasized the creative and inspirational potential of lucid music dreams, which is worth further investigation. Combining previous research on athletic practice in lucid dreams and the clues obtained from this study, it is likely that musicians could use lucid dreams to improve their skills. Future studies should further explore the potential of lucid music dreams for both creativity and performance in waking life. (PsycINFO Database Record (c) 2018 APA, all rights reserved)